2019
DOI: 10.1038/s41598-019-40700-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Plasma-Treated Corn Seeds under Realistic Conditions

Abstract: In this study, the effect of the plasma treatment on corn seeds is investigated. Corn seeds were treated uniformly without burning or blackening by three kinds of plasma apparatus: RF plasma in vacuum, microwave-driven atmospheric-pressure plasma, DBD atmospheric-pressure plasma, and two other treatments: vacuum exposure only, and using plasma-activated water in the seed coating process, to investigate growth rate changes under realistic conditions. Each treatment was performed on a total of 1512 corn seeds. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…The primary aim of the current work was to investigate the influence of H 2 O-based LPP treatment on the Bambara groundnut germination, as vacuum alone has been shown to have mixed results [26][27][28]. Furthermore, this study aimed to suggest the mechanism responsible, applying various assays such as the measurement of water uptake and electrical conductivity of the liquid used to submerge Bambara groundnut seeds.…”
Section: Introductionmentioning
confidence: 99%
“…The primary aim of the current work was to investigate the influence of H 2 O-based LPP treatment on the Bambara groundnut germination, as vacuum alone has been shown to have mixed results [26][27][28]. Furthermore, this study aimed to suggest the mechanism responsible, applying various assays such as the measurement of water uptake and electrical conductivity of the liquid used to submerge Bambara groundnut seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma treatment promotes seed germination and subsequent seedling growth, increasing the length and biomass of seedlings (Table 1). As mentioned earlier, enhanced seedling growth without changes to the germination efficiency has been also observed after plasma treatment [15,19,41,44,56,59,64]. Plasma treatment at the seedling stage has also reported, which promoted seedling growth [10,48,55,61,63].…”
Section: Effects Of Plasma On Plant Vegetative Growth and Reproductionmentioning
confidence: 55%
“…In the past 20 years, various plasma sources (dielectric barrier discharge (DBD) jet plasma, microwave discharge, radio-frequency (RF) discharge, gliding discharge) have been developed and used for treating vegetables (tomato, radish, coriander, green peas, and sunflower) and crops (rapeseed, cotton, maize, oat, wheat, mustard, soybean, legumes, and honey clover) (Table 1). Plasma treatment (direct or indirect) has enhanced seed germination in most studies, although no changes in the germination percentage were observed in several studies [15,19,41,44,56,59,64]. Plasma promoted the germination speed, overall germination percentage, or both.…”
Section: Effect Of Plasma On Seed Germinationmentioning
confidence: 92%
See 1 more Smart Citation
“…It integrates about 99 per cent of the visible universe. There are significant charge carriers in plasma that make it electrically conductive and strongly influenced by electric and magnetic fields (Ahn et al 2019, Ding et al 2011. It forms structures viz., beams, filaments and double layers under the influence of a magnetic field, (Nalwa et al 2018).…”
mentioning
confidence: 99%